If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(8) + -3x = 18 Multiply 3 * 8 24 + -3x = 18 Solving 24 + -3x = 18 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-24' to each side of the equation. 24 + -24 + -3x = 18 + -24 Combine like terms: 24 + -24 = 0 0 + -3x = 18 + -24 -3x = 18 + -24 Combine like terms: 18 + -24 = -6 -3x = -6 Divide each side by '-3'. x = 2 Simplifying x = 2
| 40+4j=2(-4-13j) | | 64=d/-8+69 | | 3x-25=x+35 | | 6n+8=5 | | xy-y=a+d | | 5x+15x-7=5(4x+4) | | (3x-2)(x+3)=-6x-4 | | (x+5)(x-5)=(x+1)(x+7)+10 | | 3(x-9)+8=62 | | 2x*7=10 | | (4a+5b)(8a-7b)= | | 260=-v+165 | | 73.543-23.683= | | (2x-1)/4=(x+5)/3 | | 2a+3=(1)/(2)(6+4a) | | 7X=7.5 | | 13x+1=13x+59 | | 5+2(y-7)=3(y+1)-2 | | 2n-7/3 | | 2(2-2)=4 | | 25000-20000-15000=x | | 64-v=231 | | 2x+x+8=6x-3x+8 | | x/6-5 | | 22=-x+215 | | 8P+2=-3P-15 | | 25000-x=20000+15000 | | 7x-5x-7x+1=6x-6x-7 | | 3(x+3)=7x+6-4x+3 | | ma-st=5m+2 | | 10x+30x-8=8(5x+7) | | 1/5x-1/5=-3 |